Inhibition of Streptococcus mutans biofilm formation using combination of nano brown anchovy (Stolephorus insularis) and calcium hydroxide - Yuanita, Tamara; Sukaton; Paramitha, Shafa Marwa Moza; Ulfadi, Bakhiitah Thufallah Putri; Salma, , Adinda Fazzahra; Setyabudi (Universitas Airlangga, 2023)
Background: One of the important virulence factors of S. mutans is the biofilm formation. Some bacteria in biofilms show resistance to antimicrobials. Therefore, the addition of nano brown anchovy (S. insularis) as antibiofilm agents can potentiate the caries and infection prevention efficacy of endodontic treatment. Purpose: To describe the effect of the combination of nano brown anchovy (S. insularis) 12% and Ca(OH)2 with a ratio of 1:1 on inhibition of S. mutans biofilm formation. Methods: Laboratory experimental research on S. mutans bacteria was carried out in vitro using the crystal violet assay method. Brown anchovy was made into nanoparticles, dissolved to a concentration of 12%, and combined with Ca(OH)2. Biofilm samples were given treatment and observed for inhibition of biofilm growth. Biofilm growth inhibition was seen from the Optical Density (OD)540nm absorbance value measured using a spectrophotometer. Results: In the group that was tested with Ca(OH)2, the average percentage in S. mutans biofilm reduction was 55%, while in the group that was tested with a combination of nano brown anchovy (S. insularis) and Ca(OH)2, the average percentage in S. mutans biofilm reduction was 61%. Conclusion: The combination of nano brown anchovy (S. insularis) 12% and Ca(OH)2 with a ratio of 1:1 can inhibit the formation of S. mutans biofilm.